2019
DOI: 10.2991/jegh.k.190522.001
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Satisfaction after Primary Health Care Centers’ Integration with Ministry of Health Hospitals, Jeddah

Abstract: A B S T R A C TIn today's competitive and media-influenced health care environment, resource utilization is driven by patient outcome.A key criterion to evaluate the quality of health care services is to assess patients' satisfaction. The objectives of this study were to compare patients' satisfaction in the first and last quarters after Primary Health Care Centers' (PHCCs) integration with Ministry of Health (MOH) hospitals in Jeddah, and to identify the factors contributing toward patient's satisfaction in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
3
17
1
Order By: Relevance
“…The second portion addressed general service satisfaction, which was separated into three sub-sections: (a) satisfaction with registration and reception (two items on registration time and public relations services), (b) general hospital facilities (four items about the hospital's peacefulness, cleanliness, physical facilities, and overall patient opinion of the facility), and (c) nurse care (three items on courtesy, cooperation, and respect). The elements of second portion of the questionnaire were adapted from another published article ( 26 ). The third portion included a total of seven items to evaluate patients' satisfaction with the pharmacy services, including medication supply and availability; patient counseling; resolving medication-related problems; setting-specific structural issues; and general pharmacy services.…”
Section: Methodsmentioning
confidence: 99%
“…The second portion addressed general service satisfaction, which was separated into three sub-sections: (a) satisfaction with registration and reception (two items on registration time and public relations services), (b) general hospital facilities (four items about the hospital's peacefulness, cleanliness, physical facilities, and overall patient opinion of the facility), and (c) nurse care (three items on courtesy, cooperation, and respect). The elements of second portion of the questionnaire were adapted from another published article ( 26 ). The third portion included a total of seven items to evaluate patients' satisfaction with the pharmacy services, including medication supply and availability; patient counseling; resolving medication-related problems; setting-specific structural issues; and general pharmacy services.…”
Section: Methodsmentioning
confidence: 99%
“…49 Integrating PC with hospitals improved PS and experience. 50 The study showed that, after the integration of PC with local hospitals, there was a significant improvement in satisfaction levels in every functional domain, such as overcrowding at the registration counters, overall improvement in PC cleanliness, improved overall general behavior of the staff, and promptness of services. 50 With regards to staff operation, on the contrary, satisfaction was seen as high with laboratory, pharmacy, radiology, and dental staff and services as well as with physicians, 29 while seen as not significantly related to receptionists' communication.…”
Section: Organizational Characteristicsmentioning
confidence: 95%
“…For laboratories under CBAHI standards, there are a total of 11 standards (56 substandard) covering the expected laboratory functions for diagnosis, treatment monitoring, evaluation, and plans for future decisions. Most of the published studies related to CBAHI standards implementation and outcomes in PHCs were focusing mainly on patient satisfaction outcomes, which is an important quality improvement tool to measure the patient experience journey [17].…”
Section: The Role Of Saudi Central Board For Accreditation Of Health Institutes (Cbahi) In Harmonizing the Healthcare Servicesmentioning
confidence: 99%